Novel Symmetrical 1,4-Disubstituted-bis-1,2,3-Triazoles: Synthesis by Double CuAAC and Cytotoxicity Evaluation - Reis, Wallace J.; Moreira, Paulo O.L.; Alves, Rosemeire B.; Oliveira, Helo H.M.; Silva, Luciana M.; Varotti, Fernando P.; Freitas, Rossimiriam P. (Current Topics in Medicinal Chemistry, 2018)
Background: A series of symmetrical 1,4-disubstituted bis-1,2,3-triazoles was prepared by double copper catalyzed Azide-alkyne Cycloaddition (CuAAC) from aliphatic bis-azides and a tetraethylene glycol bis-azide derivative. The eighteen novel compounds were evaluated in vitro for their cytotoxic activity against two human tumor cell lines: Human breast adenocarcinoma (MDA-MB 231) and ovarian adenocarcinoma (TOV-21G). Results and Conclusion: The results of colorimetric MTT assays showed that compounds 4j and 4q exhibited a better selectivity index and cell viability comparable with the standard drug doxorubicin. These compounds induced apoptosis in both tested cell lines, as assessed by BrdU assay. The results suggest that these structurally simple compounds may be promising prototypes for antitumoral agents.
Keywords: Bis-azides